2024
DOI: 10.1021/acs.est.3c07035
|View full text |Cite
|
Sign up to set email alerts
|

Photo-oxidation of Micro- and Nanoplastics: Physical, Chemical, and Biological Effects in Environments

Yanghui Xu,
Qin Ou,
Jan Peter van der Hoek
et al.

Abstract: Micro-and nanoplastics (MNPs) are attracting increasing attention due to their persistence and potential ecological risks. This review critically summarizes the effects of photo-oxidation on the physical, chemical, and biological behaviors of MNPs in aquatic and terrestrial environments. The core of this paper explores how photo-oxidation-induced surface property changes in MNPs affect their adsorption toward contaminants, the stability and mobility of MNPs in water and porous media, as well as the transport … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 242 publications
0
2
0
Order By: Relevance
“…On the one hand, reactive species were involved in the destruction of C–H, C–OH, C–C, and benzene rings, implying that a considerable portion of reactive species was consumed during the aging process prior to generation of CO. This phenomenon has also been reported in many studies. , On the other hand, combined with previous studies on DOM presenting multiple roles in organic pollutants photoaging, although the photosensitizing effect and redox cycle of DOM can induce a high level of reactive species production, reactive species scavenging brought about by its own moiety also exists simultaneously . Therefore, in PSMP photoaging, partial reactive species needed to counteract the scavenging effect so they could not directly participate in the PSMP functional group changes.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…On the one hand, reactive species were involved in the destruction of C–H, C–OH, C–C, and benzene rings, implying that a considerable portion of reactive species was consumed during the aging process prior to generation of CO. This phenomenon has also been reported in many studies. , On the other hand, combined with previous studies on DOM presenting multiple roles in organic pollutants photoaging, although the photosensitizing effect and redox cycle of DOM can induce a high level of reactive species production, reactive species scavenging brought about by its own moiety also exists simultaneously . Therefore, in PSMP photoaging, partial reactive species needed to counteract the scavenging effect so they could not directly participate in the PSMP functional group changes.…”
Section: Resultsmentioning
confidence: 64%
“…Regarding 3 DOM* (Figure F,I), the FA <1kDa exhibited a faster production rate, rapidly accumulating to the highest level within 2 h, and the steady-state concentration of 3 DOM* ([ 3 DOM*] ss ) was the highest among all tested fractions, at 1.59 × 10 –6 M (Figure S11F). Overall, the yield of reactive species was slightly higher in FA than in HA, which could be attributed to the fact that FA with abundant phenols or quinones exposed to UV irradiation can absorb photons more rapidly and promote electron shuttling between different interfaces according to the previous study, potentially providing higher quantum yields of reactive species to attack PSMP surface structures faster. Determination of •OH, 1 O 2 , and 3 DOM* during photoaging of PSMPs demonstrated that FA <1kDa exhibited superior photoactivity, and the yield of reactive species of DOM was inversely proportional to MW, which was consistent with previous reports. , Interestingly, the growth of reactive species was much larger than that of CI, possibly indicating a more complex role and fate of reactive species within the coincubation system.…”
Section: Resultsmentioning
confidence: 73%